LEGAL-THEORETICAL BASIS OF ORGANIZING MODERN GEOGRAPHY EDUCATION BASED ON ELECTRONIC INFORMATION EDUCATIONAL RESOURCES - Madjitova Jadra Abdumalikovna (European Journal of Humanities and Educational Advancements, 2023)
In this article, the reforms implemented in the use of electronic information educational resources in the improvement of the education system in our country, the opinions of scientists who conducted scientific research on the organization of modern geography education are highlighted. Conclusions and recommendations on the use of computer technologies in teaching geography are also presented